Kinerja Jalur Pedestrian di Kota Makassar - Tysa Prilya Wensy; Muh. Yamin Jinca; Arifuddin Akil (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
The existence of pedestrian ways in the central area of ​​Makassar City is expected to be able to provide optimal services to the community. The diversity of land use around Lapangan Karebosi as the city center triggered the pedestrian activities on the Jalan R.A. Kartini, Jalan Kadjaolalido, Jalan Ahmad Yani, and Jalan Jenderal Sudirman. But the function of the road space as a public space is disrupted due to misuse of land use. The purpose of this study is to identify the quality of the pedestrian path based on government policy, analyze the performance of the pedestrian path and prepare directions for pedestrian development that will be applied. The location of this study includes four road segments around the Karebosi Field in Makassar City. The research method used is descriptive qualitative method to determine the quality of pedestrian lines based on governmental policy and analysis of Level Of Service (LOS) to determine the level of pedestrian line services. The results of this study show that the Jalan Kadjaolalido and Jalan Jenderal Sudirman segments are a line in the criteria of LOS A, Jalan R.A. Kartini segmens are line in the criteria of LOS A and B, and Jalan Ahmad Yani are a line in the criteria of LOS F. Completeness of supporting facilities in all pedestrian lines is still lacking and needed an increasing in services.